“Cross-Culture Integration” Model Based on Social Capital: A Case Study in Chinese–Javanese Communities in Malang City - Astutik, Juli; Abidin, Zaenal; Deniar , Shannaz Mutiara; Al-Fatih, Sholahuddin; Norhasliza Ghapac (Indonesian Journal of Legal Community Engagement, 2025)
This article discusses cross-culture integration between Javanese and Chinese communities in Malang City, East Java, Indonesia. How social capital can construct personal and social backgrounds with very different backgrounds can shape cross-cultural integration between the two ethnicities. The research was conducted using a qualitative approach, with a descriptive type. The research subjects were Javanese and Chinese people in Malang City, East Java. Data collection was carried out by observation, interviews, documents, and focus group discussions (FGD). The results of the study show that: social capital (trust, values/norms and networks) is strength, the basic foundation in realizing cross-cultural integration between ethnic Chinese-Javanese and can maintain harmonious relations and avoid conflicts. The strength of social capital can be identified through the elements inherent in the social structure of the community, such as: trust, values, and networks. The implementation of the strength of social capital as an adhesive, as well as a bridge/liaison in interaction gave birth to cultural acculturation as a form of cross-cultural integration of ethnic Chinese and Javanese in Malang City. The recommendations in this study are: (1) The model found in cross-culture integration based on social capital in the Chinese-Javanese community in Malang City can be used as a model in understanding cross-cultural differences between the two ethnicities but can live side by side with each other, (2) Improving values/norms of togetherness between the two ethnicities, through strengthening "shared identity" as citizens of Malang City, (3) Forming and developing networks in the economic, social, cultural and defense fields continuously and sustainably. Based on the results of this study, it can be recommended that to anticipate the disintegration of the nation, it is necessary to strengthen social capital from various ethnic groups in various fields of life.